2022
DOI: 10.1017/cts.2022.408
|View full text |Cite
|
Sign up to set email alerts
|

Changing the face of academic medicine: an equity action plan for institutions

Abstract: In recent years, there have been concerted efforts to better recruit, support, and retain diverse faculty, staff, and trainees in academic medicine. However, many institutions lack comprehensive and strategic plans to provide support to retain and recruit individuals from historically underrepresented groups. In this article, we itemize specific mechanisms through which institutions can support diverse individuals with the goal of improving inclusion and belonging in the workforce to better reflect the diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…On a broad institutional level, the academic university implements many of the best practices listed in Enders and colleagues’ recommendations for a comprehensive DEI action plan, such as a biannual climate survey and incorporating best practices in addressing bias in search committees. However, because we operate in a very large matrixed health science institution, it is imperative that DEI action plans are further refined at the departmental level to address unique needs and maximize impact [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…On a broad institutional level, the academic university implements many of the best practices listed in Enders and colleagues’ recommendations for a comprehensive DEI action plan, such as a biannual climate survey and incorporating best practices in addressing bias in search committees. However, because we operate in a very large matrixed health science institution, it is imperative that DEI action plans are further refined at the departmental level to address unique needs and maximize impact [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher frequency grant submission and resubmission have been linked to funding success, and prior studies have reported that women, in aggregate, and Black faculty submit fewer grants than their counterparts . Investment in both early and mid-career meaningful mentorship initiatives for Black and women faculty will be essential to improve funding longevity and reduce the inequitable ethnic and racial distribution of NIH funding allocated to first-time PIs and among more established SPIs . Such programs may include expansion of diversity supplements for early-career faculty, developing mentoring networks for female and Black faculty, and incentivizing diverse team-based science through additional emphasis in program grants and multiple principal investigator awards.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-bias training can help team members understand that while having a bias might be part of the human condition, awareness can be key to avoiding a hidden bias becoming an unfair barrier that stunts the opportunities or success of others (Enders et al, 2022). While all individuals have bias, awareness of that bias is not universal.…”
Section: Anti-bias Training Can Help Illuminate An All Too Human Char...mentioning
confidence: 99%